2020
DOI: 10.1126/sciadv.aba1705
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Förster resonance energy transfer: A new paradigm for electrically driven quantum dot random lasers

Abstract: The many distinct advantages of random lasers focused efforts on developing a breakthrough from optical pumping to electrical pumping. However, progress in these is limited due to high optical loss and low gain. In this work, we demonstrate an electrically pumped quantum dot (QD) random laser with visible emission based on a previously unexplored paradigm named coherent Förster resonance energy transfer (CFRET). In the CFRET process, when a coherent photonic mode is formed because of multiple scattering of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…This prediction of ultrafast FRET explains the observation of sharp peaks from bulk-like CsPbBr 3 particles (acceptors) located on top of the superlattices (donor) aged in air by means of, e.g., FRET-assisted lasing. 97,98 Despite the good agreement, large variations in the calculated τ ET necessitate careful examination when using the FRET model. In addition to the uncertainty induced by estimating d, errors could propagate from experimentally determined values when recovering the prefactors in eq 2.…”
Section: Resultsmentioning
confidence: 99%
“…This prediction of ultrafast FRET explains the observation of sharp peaks from bulk-like CsPbBr 3 particles (acceptors) located on top of the superlattices (donor) aged in air by means of, e.g., FRET-assisted lasing. 97,98 Despite the good agreement, large variations in the calculated τ ET necessitate careful examination when using the FRET model. In addition to the uncertainty induced by estimating d, errors could propagate from experimentally determined values when recovering the prefactors in eq 2.…”
Section: Resultsmentioning
confidence: 99%
“…The property of bright illuminations with low spatial coherence leads RLs to reach a significant achievement in imaging and display applications 1 6 . Except for lightning and imaging, RLs can also be used in optical sensors and optoelectronic devices 6 10 . 0D,2D, 3D heterostructures or polymers have been successfully developed for several optoelectronic applications 11 16 .…”
Section: Introductionmentioning
confidence: 99%
“…0D,2D, 3D heterostructures or polymers have been successfully developed for several optoelectronic applications 11 16 . Among them, 0D quantum dots (QDs), 2D graphdiyne, perovskite, metal–organic framework (MOF), and wrinkled polymers 10 , 17 20 , have been investigated as the light scattering materials of RLs. To facilitate the practical applications of RLs, the strategy to reduce their threshold becomes a critical issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the practical applications of RLs, the strategy to reduce their threshold becomes a critical issue. Several methods were developed to reduce the threshold of RLs in combination with plasmonic nanoparticles, re ective mirrors, or uorescence resonant energy transfer (FRET) [5,[9][10][11][12][13]. Recently, Yuan et al reported plasmonic TiN nanoparticles enhanced lowthreshold random lasing from dye-doped nematic liquid crystals [13].…”
Section: Introductionmentioning
confidence: 99%